Decline in Pediatric Emergency Department Behavioral Team Activations After Institution of an Agitation Protocol. Issue 4 (April 2021) - Pavlov, Hannah; Santillanes, Genevieve; Claudius, Ilene
Abstract : Objective: Aggressive behavior among pediatric patients with psychiatric complaints in emergency departments is a growing problem. An agitation protocol was instituted in 1 pediatric emergency department to provide scaled recommendations for differing levels of aggression. The study objective was to determine if the frequency of activation of an emergency behavioral response team changed after protocol initiation. Methods: A protocol for escalating management of agitation in pediatric patients was introduced in February 2016. The electronic medical record was queried for subsequent behavioral response team activations over the next 16 months. Patient demographics and specific features surrounding the activation were retrospectively recorded from the medical record, including length of stay, medications administered, and documented deescalation techniques. Frequency and features of behavioral team activations were compared with activations from a period before the planning and implementation of the protocol (May 2014 to May 2015). Results: Twenty-one patient visits were found to require behavioral response team activation over 16 months, compared with 31 for the 13-month preprotocol period. Attempts at verbal/ environmental redirection were seen in 77% and deescalation by medication administration before the activation occurred in 14% of patients. During the behavioral team activation, 81% of the patients were given psychiatric medications and 81% were placed in physical restraints. Conclusions: A decrease from a baseline of 2.4 to 1.3 behavioral response team activations per month, or a 46% decline, was noted following the institution of a clinical protocol for pediatric agitation.